Occupational Balance in Families: The Lived Experience of Dual Earner Parents and School-Aged Children - Ranger, Marie-Christine (Université d'Ottawa / University of Ottawa, 2022)
Parents in dual earner families with school-aged children report significant time constraints. Occupational balance refers to the distribution of time in various occupations in accordance with one’s values and it has been related to well-being. While occupational balance has been studied from an individual perspective, no study to date has taken a family perspective. This research explores the lived experience and meaning of occupational balance for dual earner parents and school-aged children. Multiple perspectives were obtained to capture family occupational balance as well as individual occupational balance. This research contributes to a greater appreciation of the complex phenomenon of occupational balance. Furthermore, it adds to the ongoing conversation in occupational science on the relational aspects of occupation. For this interpretive phenomenological research, semi-structured interviews were used with parents and photo-elicitation interviews with children. Four families were recruited, for a total of 18 participants. Additional methods of data collection included individual daily schedules and a family occupational map. Lived existentials and the dimensions of occupation were used as analytical frameworks to understand the phenomenon of occupational balance. Findings reveal that family occupational balance is experienced through the theme of togetherness and enacted in two occupations: the family dinner and family leisure. For adults and older siblings, individual occupational balance is experienced through refocusing on self as illustrated in intentional activities; while playing, feeling good and having fun was central to the experience of individual occupational balance in younger siblings. A reflection on these findings is provided through 3 essences of the experience of occupational balance in families: intention, restoration, and equity. Implications for occupational therapy and occupational science highlight the dynamic and relational aspects of occupational balance in families. Unique contributions include the 3 essences which are more evocative, discernable, and therefore more applicable to research and practice than the taken for granted phenomenon of occupational balance.
Keywords: occupational balance; family; phenomenology